Tree snails \(Amphidromus\) Albers, 1850 (Pulmonata: Camaenidae) collected in Vietnam - Do, Van Nhuong; Dinh, Dieu Thuy; Do, Duc Sang; Nguyen, Thanh Tung; Le, Hung Anh; Bogan, Arthur E.; Do, Van Tu (Academia Journal of Biology, 2024)
The paper presents results on tree snails based on samples collected from various parts of Vietnam during the period of 2008–2022. As a result, 14 Amphidromus species were recorded, which increased the diversity of the genus in Vietnam to a total of 27 species. Four species were new country records including Amphidromus atricallosus perakensis, Amphidromus leucoxanthus, Amphidromus perversus natunensis, and Amphidromus areolabiatus. Almost all 14 species were found in the south, while only Amphidromus roseolabiatus was recorded in the north. The great variation in the shell morphology of these tree snails required an integrative taxonomic approach to better understand the species diversity of the genus Amphidromus in Vietnam.